2010
DOI: 10.1016/j.tripleo.2010.02.033
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of use of absorbable plate in combination with self-setting α-tricalcium phosphate for orthognathic surgery

Abstract: An experimental study of use of absorbable plate in combination with self-setting α-tricalcium phosphate for orthognathic surgery Abstract Purpose: The purpose of this study was to histologically and immuno-histochemically evaluate bone formation using both of self-setting α-tricalcium phosphate (α-TCP; BIOPEX ® ) and absorbable plate (Super FIXSORB ® -MX) in rabbit cranium bone.Study design: Adult male Japanese white rabbits (n=16, 12-16 weeks, 2.5-3.0 kg) were used. The surgical defects were made in the nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Although titanium is an effective biomaterial, it does not exhibit suitable absorption and must be removed by surgery. However, uHA/PLLA has been developed as a potentially useful biological material showing good absorption and bone conductivity; therefore, this material may facilitate bone tissue repair . Moreover, studies have reported the complete process of bioresorption and bone replacement of rods made of forged composites of unsintered hydroxyapatite particles/poly‐ l ‐lactide (F‐u‐HA/PLLA) implanted in the femoral medullary cavities of rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although titanium is an effective biomaterial, it does not exhibit suitable absorption and must be removed by surgery. However, uHA/PLLA has been developed as a potentially useful biological material showing good absorption and bone conductivity; therefore, this material may facilitate bone tissue repair . Moreover, studies have reported the complete process of bioresorption and bone replacement of rods made of forged composites of unsintered hydroxyapatite particles/poly‐ l ‐lactide (F‐u‐HA/PLLA) implanted in the femoral medullary cavities of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…However, uHA/PLLA has been developed as a potentially useful biological material showing good absorption and bone conductivity; therefore, this material may facilitate bone tissue repair. [26][27][28][29] Moreover, studies have reported the complete process of bioresorption and bone replacement of rods made of forged composites of unsintered hydroxyapatite particles/poly-L-lactide (F-u-HA/PLLA) implanted in the femoral medullary cavities of rabbits. These studies showed that morphological changes during biodegradation and bone replacement in the proximal medullary cavity lasted for up to 4.5 years and that the molecular weight and bending strength decreased to 50 kDa and 200 MPa after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this clinical study, a previous study using rabbit suggested that the use of an absorbable plate (Super FIXSORB®-MX) in combination with Biopex® was useful and both Super FIXSORB®-MX and Biopex® could provide adequate bone regeneration and maintain strength and stability in the surgical bone space (Okabe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they used the self-setting α-tricalcium phosphate (α-TCP; Biopex ® ) to fill the bone defects postoperatively, thus improving bone regeneration and long-term stability. A rabbit model study confirmed that the use of u-HA/PLLA plates with this material was beneficial, i.e., it could provide sufficient bone regeneration while maintaining strength and fixation in the surgical bone defect [ 193 ]. A 2013 study evaluated the postoperative changes in maxillary stability after Le Fort I osteotomy using u-HA/PLLA devices with or without α-TCP [ 194 ].…”
Section: Clinical Applications Of U-ha/plla In Oral and Maxillofacial Surgerymentioning
confidence: 99%